Cultural issues in post‐disaster reconstruction: the case of Typhoon Morakot in Taiwan. Issue 4 (8th January 2016) - Lin, Jen‐Jen; Lin, Wan‐I
Abstract : Most members of Taiwan's indigenous communities live in areas that are prone to natural disasters. Yet, due to their marginalised cultural, economic and political status, each time such calamities strike, any assistance they receive is usually provided without considering their actual needs. The areas hardest hit by Typhoon Morakot in August 2009 were the indigenous villages in the southern and eastern parts of the island. After the initial emergency relief efforts had been completed, there remained the highly challenging task of reconstruction and the resettlement of those who lost their homes and livelihoods. This paper examines the cultural conflicts that arose during the reconstruction process, with special emphasis on the participation of Taiwan's indigenous communities and their capacity for resilience. It was found that community participation and identification are key issues in effective disaster governance.